SERVING JIHAD: HAMAS AND THE INSTRUMENTALITY OF VIOLENCE IN THE MIDDLE EAST - Romaniuk, Scott Nicholas; Wasylciw, Joshua K. (European Scientific Journal, ESJ, 2012)
Since it emergence on the international scene more than two decades ago, Hamas has stuck to its guns, labouring tirelessly to establish a Muslim state based upon the principles of Jihad, and to propagate Jihadi values in all aspects of life as outlined in its 1988 Charter. On its path to realize its ultimate goals, and acting upon the credo that “Islam is the Solution,” Hamas has persisted in killing and maiming Israelis, civilians and soldiers alike, through a variety of violent means. This article explores the Hamas as a longstanding terrorist organization and its instrumentality of violence in the Middle East. The argument is presented that although it is seen by some as a legitimate political and social movement Hamas has not departed from its violent practices in order to achieve its political objectives, and does not seem to qualify as a new and dynamic actor in the Middle East simply because it was elected to govern in Gaza.